METHODOLOGICAL PRINCIPLES OF ACCOUNTING AND TAXATION OF RESPONSIBLE STORAGE AND RENT OPERATIONS - RASSOLENKO, Yuliia; BIЕLOZERTSEV, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today's conditions of a shortage of own financial resources in enterprises and the lack of the possibility of obtaining loans, the most affordable and effective way of financing the current needs in the organization of the enterprise's activities is the lease of fixed assets. Places for storing stocks and warehouses are needed by enterprises of almost any industry and field of activity. The easiest way to get such non-negotiable assets at your disposal to ensure your specialized activity is to enter into a lease relationship.On the other hand, in the current crisis conditions, for some enterprises and organizations, even the use of lease schemes of relationships can be a burdensome process that requires the diversion of resources to the maintenance of leased space. For a business whose activity is connected with certain material values, the need to organize the storage of its products or goods in a warehouse is extremely important. Renting or buying warehouse space in the short term may not be profitable for the enterprise. It is necessary to organize unloading and loading of goods or products, purchase warehouse equipment, install video surveillance and security alarms, hire staff. One of the work organization options is the outsourcing of warehouse processes and the use of a responsible storage service.This article examines the importance of leasing primary assets as a strategic mechanism to meet the current needs of businesses, especially in the context of limited credit opportunities and a deficit in their own financial resources. The authors thoroughly analyze various aspects and forms of leasing relationships, including full-service leasing, "pure" and "general" leasing, as well as their specific characteristics. A significant role in the study is the impact of modern information technologies on leasing relationships, particularly through the concept of "sharing". The issue of responsible storage as a key component of the logistical chain, which is of great importance for businesses, is separately highlighted. The authors propose new approaches to the methodology of reflecting costs for services of responsible storage and leasing, aimed at increasing the accuracy of calculations for the tax base of corporate income tax. The article makes a substantial contribution to the understanding of the complexity of leasing relationships and their impact on the financial stability of enterprises in modern economic conditions.
Keywords: leasing; responsible storage; logistics; information technology in leasing; cost accounting methodology